2019
DOI: 10.1002/cncy.22170
|View full text |Cite
|
Sign up to set email alerts
|

CytoLyt fixation significantly inhibits MIB1 immunoreactivity whereas alternative Ki‐67 clone 30‐9 is not susceptible to the inhibition: Critical diagnostic implications

Abstract: Background The Ki‐67 proliferation marker has multiple diagnostic and prognostic applications. Although several clones to the Ki‐67 antigen are commercially available, the MIB1 clone is widely recommended in the surgical pathology literature for neuroendocrine tumors. In our cytopathology practice, we have encountered unexpectedly low MIB1 immunoreactivity in CytoLyt‐fixed cell blocks (CBs). The current study evaluated the impact of fixatives, CB processing, and immunocytochemical (ICC) procedures on Ki‐67 imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…Other studies have PD-L1 Immunostaining in Cytology/Koomen et al shown a detrimental effect of CytoLyt fixation on IHC detection of some antigens, such as thyroid transcription factor-1 (TTF-1) 18 and Ki-67. 21 A study by Lloyd et al 30 demonstrated a similar effect on PD-L1 staining, with CytoLyt fixation showing poor PD-L1 immunostaining results. Gosney at al 31 observed no effect of alcohol-based fixatives, including CytoLyt, on PD-L1 immunostaining with the 22C3 pharmDx assay in cytology specimens.…”
Section: Discussionmentioning
confidence: 91%
“…Other studies have PD-L1 Immunostaining in Cytology/Koomen et al shown a detrimental effect of CytoLyt fixation on IHC detection of some antigens, such as thyroid transcription factor-1 (TTF-1) 18 and Ki-67. 21 A study by Lloyd et al 30 demonstrated a similar effect on PD-L1 staining, with CytoLyt fixation showing poor PD-L1 immunostaining results. Gosney at al 31 observed no effect of alcohol-based fixatives, including CytoLyt, on PD-L1 immunostaining with the 22C3 pharmDx assay in cytology specimens.…”
Section: Discussionmentioning
confidence: 91%
“…7 The type of fixative can cause decreased antigenicity of certain antibodies, including other nuclear markers such as MIB1 and ER as well as cytoplasmic stains such as S100. [16][17][18] This decrease in antigenicity might be attributed to differences in the effect of each fixative on the cells obtained. Formalin fixes specimens through the formation of intramolecular and intermolecular cross-links, whereas alcohol removes water from the free carboxyl, hydroxyl, amino, amido, and imino groups of the proteins, resulting in protein coagulation and tissue shrinkage.…”
Section: Discussionmentioning
confidence: 99%
“…Although immunostains are generally validated using formalin‐fixed, paraffin‐embedded tissue, several cytology laboratories use material previously fixed in an alcohol‐based medium before cell block processing . The type of fixative can cause decreased antigenicity of certain antibodies, including other nuclear markers such as MIB1 and ER as well as cytoplasmic stains such as S100 . This decrease in antigenicity might be attributed to differences in the effect of each fixative on the cells obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many laboratories use different fixatives and have different methods of cellblock preparations or indications to create a cellblock. The effects of fixation in downstream analysis, has become a well‐documented fact in diagnostic cytology 6,7 . There are still questions among cytopathologists on whether a cell block should be part of cytology preparations.…”
Section: 20164 Category Criteria Category Criteriamentioning
confidence: 99%